«SYSTEM OF LIFE MEANINGS» TECHNIQUE - V. Yu. Kotlyakov (Вестник Кемеровского государственного университета, 2013)
The article aims at examining the issues related to the practice of using the "System of Life Meanings" (SLM) technique: the application of the SLM technique in scientific research, the purpose and the options of its usage, the correlation of the SLM technique and M. Rokich’s methodologies, the changes in the methods of SLM technique, the electronic version of the SLM technique are discussed.